Multiparameter analysis of biomarkers in the laboratory diagnosis of early rheumatoid arthritis - Aleksandr Aleksandrovich Novikov; E N Aleksandrova; A N Gerasimov; M V Cherkasova; D E Karateev; E L Luchikhina; E L Nasonov (Научно-практическая ревматология)
Subjects and methods. 102 patients with early RA (79 women and 23 men; median age 51 years [41 to 62, 25th to 75th percentile]; disease duration 4 months [2.5 to 6.0]; DAS28 5.4 [4.1 to 5.9]) were examined. A comparison group consisted of 616 patients including 27 with systemic lupus erythematosus, 15 with Sjö gren’s syndrome, 25 with ankylosing spondyloarthritis; 33 with osteoarthritis, 20 with overlap syndrome, 9, 22, and 168 patients with gouty, psoriatic, and undifferentiated arthritis, respectively; as well as 297 healthy donors matched with the examinees for gender and age. The concentrations of 36 biomarkers were measured by an immunonephelometric method, enzyme immunoassay, and xMAP technology. The values of one variable from others were predicted using a multiple linear regression method (multivariate analysis). Results. The strongest predictors of early RA, such as the concentrations of interleukin-6, C-reactive protein, granulo-cyte-macrophage colony-stimulating factor, interferon-γ (IFN-γ), IFN^-inducible protein, anti-cyclic citrullinated peptide antibodies, were identified and a candidate for MDI was developed for early RA (MIRRA). After thorough validation, MIRRA may be regarded as a precision serological assay for the early diagnosis of RA. Conclusion. The development of MDI having a higher diagnostic precision than routinely used biomarkers is imperative for early RA diagnosis that allows one to initiate active antirheumatic therapy that is able to effectively delay progressive joint injury.